Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.7759/cureus.4235
|View full text |Cite
|
Sign up to set email alerts
|

Pancytopenia: A Rare and Unusual Initial Presentation of Breast Cancer

Abstract: Bone marrow metastasis with profound pancytopenia is an extremely uncommon presentation of breast cancer. Advanced breast cancer can frequently metastasize to bone marrow, but bone marrow failure is not typically seen. Very limited data exist regarding the appropriate management of patients with metastatic breast cancer with profound pancytopenia. Our patient’s initial presentation of anemia and thrombocytopenia was a diagnostic dilemma, later confirmed as metastatic breast cancer on bone marrow biopsy. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Recent reports have observed certain rare causes of pancytopenia that include breast carcinoma, myxedema coma, or Stevens-Johnson syndrome. [232425] Although no such cause was reported in the present study, it is necessary that clinicians and the pathologists should be aware of such rare causes of pancytopenia. Similar to our study, Le Clef et al .…”
Section: Discussionmentioning
confidence: 67%
“…Recent reports have observed certain rare causes of pancytopenia that include breast carcinoma, myxedema coma, or Stevens-Johnson syndrome. [232425] Although no such cause was reported in the present study, it is necessary that clinicians and the pathologists should be aware of such rare causes of pancytopenia. Similar to our study, Le Clef et al .…”
Section: Discussionmentioning
confidence: 67%
“…40 Psychological pressures such as the Review Article SMJ emergence of negative feelings such as shock, anxiety, anger, protest, and depression are also experienced by patients, considering the long duration of treatment, having high pain effects, and worrying about expensive treatment costs. [41][42][43] In this study, the overall aim is to consolidate the research area of health-related quality of life in breast cancer. The current study clearly found that the trend was an increase in publications during the last decade of the study period.…”
Section: Discussionmentioning
confidence: 99%